LIFTing Corporate Governance in Public Private Partnerships - Mutvalli, Raaqib (2006)
The last twenty years has seen a significant shift on two inter-related ideas within the Public Sector. The introduction of more market-based mechanisms as part of the New Public Management reforms has seen an increasing role for the private sector in the public services arena. The second major change has been a greater awareness of the public sectors need to be accountable to its stakeholders leading to the use of governance mechanisms usually seen in the private sector. The health sector has been one of the most active in the introduction of these double sided reforms. This study looks at the issues that have been raised by the reforms in the governance of Public Private Partnerships. The focus is on NHS LIFT which brings together the public and private sector in an equity joint venture with the aim of tackling the problem of underinvestment in primary care facilities. There was seen to be a lack of literature on this topic with only a handful of authors researching such a topical issue. Using semi structured interviews; key stakeholders at national and local levels, from both the public and private sector were interviewed to elicit their views on the issues and challenges they faced with regard to the governance of this new organisational form. The issues that were found were mainly of understanding and trust between the two parties. Differences in views between national level and local level were also a common theme. However, it was recognised that the governance arrangements in this model are an improvement upon previous PFI models.